Infinitive Structure of Kurdish Language According to New Theories of Language (Raparin Journal of Humanities (RJH), 2025)
It is obvious that the topic of the infinitive, whether as function and role or as structure and appearance, is one of the main and basic foundations of the linguistic units of most languages in the world, this is based on its participation as the infinitive or as the verb itself will actively engage in the language structure. As a consequence of that, many different perspectives and opinions have been expressed about infinitives in these languages. In this research, we tried to explain some of the rules and constitutions of the structure of infinitives in Kurdish according to new language theories and present necessary and proper examples in this regard. We compared those rules and forms of infinitive structure in other languages like English and also in Arabic as well, to demonstrate more about infinitive structure, because Incorporation languages work similarly in some characteristics, this similarity is significantly parallel in Kurdish and English. On top of that, the function of the infinitives and the roles they can turn into in the structure of phrases and sentences are discussed and investigated. At the end of the research, we reached several conclusions, followed by the references, the abstract and title of the research in English.